Field notes contributed by Barbara L. Wilson, spring 1980 - Wilson, Barbara L.et al (1980)
List of birds and locations contributed by Barbara L. Wilson. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed